Polyurethane foam and its manufacturing method

Incorporating sodium hydrogen carbonate and organic acids into polyurethane foam raw materials with specific ratios creates a double cell structure that enhances sound absorption and prevents scorching, ensuring high-quality, lightweight foams.

JP7621403B2Active Publication Date: 2025-01-24INOAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023045857
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-01-24
Estimated Expiration
2038-04-11

AI Technical Summary

Technical Problem

Polyurethane foams containing a large amount of water as a blowing agent experience high exothermic temperatures during foaming, leading to scorching and decreased quality.

Method used

Incorporating sodium hydrogen carbonate and optionally an organic solid acid like citric acid into the polyurethane foam raw materials, with a water content of 10 parts by weight or more and an isocyanate index of 100 or more, to create a double cell structure that attenuates sound and suppresses temperature rise through endothermic reactions.

Benefits of technology

The resulting polyurethane foam exhibits excellent sound absorption properties and maintains good quality by preventing scorching, while being lightweight due to the double cell structure and controlled temperature rise.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621403000001
    Figure 0007621403000001
  • Figure 0007621403000002
    Figure 0007621403000002
  • Figure 0007621403000003
    Figure 0007621403000003
Patent Text Reader

Abstract

The object of the present invention is to provide a polyurethane foam that has sound-absorbing properties, is lightweight, has good quality, and is suitable for use in furniture, building materials, vehicle interior materials, etc. [Solution] In a polyurethane foam obtained from polyurethane foam raw materials containing polyol, isocyanate, blowing agent, and catalyst, the polyurethane foam raw materials contain sodium bicarbonate, the blowing agent water is 10 parts by weight or more per 100 parts by weight of polyol, and the isocyanate index is 100 or more, resulting in a polyurethane foam that is sound-absorbing, lightweight, and of good quality.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lightweight polyurethane foam having sound absorbing properties and a method for producing the same. [Background technology]

[0002] Polyurethane foams obtained from polyurethane foam raw materials containing polyol, isocyanate, blowing agent, and catalyst are widely used in furniture, building materials, vehicle interior materials, and the like.

[0003] A polyurethane foam containing a large amount of water (7 to 17 parts by weight per 100 parts by weight of polyol) as a blowing agent is known as a lightweight polyurethane foam having sound absorbing properties (Patent Document 1, claim 7).

[0004] However, polyurethane foams that contain a large amount of water as a blowing agent generate high heat during foaming, which can cause the polyurethane foam to scorch (burn, scorch), resulting in a deterioration in quality. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5204754 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above-mentioned points, and an object of the present invention is to provide a polyurethane foam which has sound absorbing properties, is lightweight and has good quality, and a method for producing the same. [Means for solving the problem]

[0007] The first aspect of the invention is a polyurethane foam obtained from a polyurethane foam raw material containing a polyol, an isocyanate, a blowing agent, and a catalyst, wherein the polyurethane foam raw material contains sodium bicarbonate, the blowing agent water is 10 parts by weight or more per 100 parts by weight of the polyol, and the isocyanate index is 100 or more.

[0008] The second aspect of the invention is the first aspect of the invention, wherein the sodium hydrogen carbonate is 5 to 30 parts by weight based on 100 parts by weight of the polyol.

[0009] The invention according to a third aspect is the invention according to the first or second aspect, characterized in that the polyurethane foam raw material contains an organic solid acid together with the sodium bicarbonate.

[0010] A fourth aspect of the invention is the third aspect of the invention, wherein the amount of the organic solid acid is 1 / 30 to 1 / 60 of the amount of the sodium hydrogen carbonate.

[0011] A fifth aspect of the invention is the third or fourth aspect of the invention, characterized in that the organic solid acid is citric acid and / or malic acid.

[0012] The invention of a sixth aspect is a method for producing a polyurethane foam by mixing and reacting polyurethane foam raw materials containing a polyol, an isocyanate, a blowing agent, and a catalyst, characterized in that the polyurethane foam raw materials contain sodium bicarbonate, the blowing agent water is present in an amount of 10 parts by weight or more per 100 parts by weight of the polyol, and the isocyanate index is 100 or more. Effect of the Invention

[0013] In the present invention, the polyurethane foam has a cell region 11 in which cells (pores) are aggregated (hereinafter referred to as a "double cell region") as shown in Figure 1. The cell region other than the double cell region 11 of the polyurethane foam is referred to as a matrix cell region 12.

[0014] Generally, sound transmitted through a porous region is considered to be a solid-propagated wave that propagates through the porous resin skeleton and an air-propagated wave that propagates through the voids in the air bubbles. In the polyurethane foam of the present invention having a double-cell region, the innumerable cells that are intricately intertwined and aggregated form a region in which both solid-propagated waves and air-propagated waves are easily attenuated, and the sound is attenuated when it passes through the region, resulting in a large sound-absorbing effect. On the other hand, in a polyurethane foam having a normal cell structure without a double-cell region, the intricately intertwined multiple cells are not aggregated, so sound passes through the foam, is less attenuated, and has a smaller sound-absorbing effect than the polyurethane foam having a double-cell region of the present invention.

[0015] In the present invention, since 10 parts by weight or more of water is used as the blowing agent, there is a concern that the reaction heat generation temperature will become high during the production of polyurethane foam. However, the sodium bicarbonate contained in the polyurethane foam raw materials is decomposed by the heat generated during the production of polyurethane foam to produce water, and the temperature rise is suppressed by the latent heat of evaporation (heat of vaporization) of the water. As a result, the inside of the polyurethane foam is not exposed to high temperatures, and a good quality polyurethane foam that is less likely to scorch, is lightweight, and has little discoloration can be obtained.

[0016] The amount of sodium hydrogen carbonate is preferably 5 to 30 parts by weight per 100 parts by weight of polyol. By setting the amount of sodium hydrogen carbonate within this range, the temperature rise due to heat generation can be effectively suppressed, and a polyurethane foam with good quality can be obtained.

[0017] It is also preferable that the polyurethane foam raw material contains an organic solid acid together with sodium hydrogen carbonate. During the production of polyurethane foam, the sodium hydrogen carbonate and the organic solid acid first cause a first-stage endothermic reaction, suppressing the temperature rise.

[0018] When the organic solid acid is citric acid, the first-stage endothermic reaction is as shown in Figure 2, where the reaction between sodium bicarbonate and citric acid produces trisodium citrate, water, and carbon dioxide. The heat absorbed during this process suppresses the temperature rise caused by the reaction of the polyurethane foam raw materials.

[0019] Furthermore, sodium bicarbonate that was not consumed in the first-stage endothermic reaction undergoes the second-stage endothermic reaction shown in Figure 2 due to heat generated by the subsequent reaction of the polyurethane foam raw materials, thereby further suppressing the temperature rise due to the reaction of the polyurethane foam raw materials. In the second-stage endothermic reaction, sodium bicarbonate that was not consumed in the first-stage endothermic reaction is thermally decomposed into sodium carbonate, water, and carbon dioxide.

[0020] The first-stage endothermic reaction and the second-stage endothermic reaction when the organic solid acid is malic acid are as shown in FIG. In addition, water and carbon dioxide are generated as the reaction decomposition products of sodium bicarbonate and organic solid acid (e.g., citric acid or malic acid). The water generated evaporates and the carbon dioxide is naturally released from the polyurethane foam, making the polyurethane foam lighter. [Brief description of the drawings]

[0021] [Figure 1] 1 is a photograph of the surface of a polyurethane foam of the present invention taken with a microscope at 20x magnification. [Diagram 2] FIG. 1 is a diagram showing an endothermic reaction between sodium bicarbonate and citric acid. [Diagram 3] FIG. 1 is a diagram showing an endothermic reaction between sodium bicarbonate and malic acid. [Figure 4] 1 is a table showing the compositions and physical property measurement results of Examples and Comparative Examples. [Diagram 5] 1 is a table showing the measurement results of the seven-point average sound absorption coefficient. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The polyurethane foam of the present invention is produced by mixing and reacting polyurethane foam raw materials containing a polyol, an isocyanate, a blowing agent, a catalyst, sodium bicarbonate, and preferably an organic solid acid.

[0023] As the polyol, a polyol for polyurethane foam can be used. For example, any of polyether polyol, polyester polyol, and polyether ester polyol may be used, and one or more of these may be used.

[0024] Examples of polyether polyols include polyether polyols obtained by adding alkylene oxides such as ethylene oxide (EO) and propylene oxide (PO) to polyhydric alcohols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, neopentyl glycol, glycerin, pentaerythritol, trimethylolpropane, sorbitol, and sucrose.

[0025] Examples of polyester polyols include polyester polyols obtained by polycondensation of an aliphatic carboxylic acid such as malonic acid, succinic acid, or adipic acid, or an aromatic carboxylic acid such as phthalic acid, and an aliphatic glycol such as ethylene glycol, diethylene glycol, or propylene glycol. Examples of the polyether ester polyol include those obtained by reacting the above-mentioned polyether polyol with a polybasic acid to form a polyester, and those having both polyether and polyester segments in one molecule.

[0026] As for the polyol, it is preferable to use one or more polyols having a hydroxyl value (OHV) of 20 to 300 mgKOH / g, a functionality of 2 to 6, and a weight average molecular weight of 500 to 15,000.

[0027] As the isocyanate, an aliphatic or aromatic polyisocyanate having two or more isocyanate groups, a mixture thereof, and a modified polyisocyanate obtained by modifying them can be used. As the aliphatic polyisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexamethane diisocyanate, etc. can be mentioned, and as the aromatic polyisocyanate, toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate, xylylene diisocyanate, polymeric MDI (crude MDI), etc. can be mentioned. In addition, prepolymers can also be used.

[0028] The isocyanate index (INDEX) is preferably 100 or more, more preferably 120 or more, with the upper limit being 200 or less.

[0029] Now, let us look at the temperature change over time accompanying the foaming and hardening of polyurethane foam. In the initial reaction, the reaction between the polyol component and isocyanate is promoted, and the temperature of the foam rises with an exothermic reaction. In particular, heat tends to accumulate inside the foam, and the temperature rises significantly. During this time, urethane bonds are predominantly generated by the polyol and isocyanate, and the matrix cell region 12 is formed. Then, when the temperature inside the foam reaches the decomposition temperature of sodium bicarbonate, the sodium bicarbonate finally decomposes and generates carbon dioxide gas and water. This generated water reacts with the isocyanate. The isocyanate assumed to react here is the isocyanate other than the isocyanate that was consumed by reacting with the polyol component to generate the urethane bond in the initial reaction. In other words, it is the isocyanate equivalent to an amount with an isocyanate index exceeding 100. It is assumed that when the water generated from sodium bicarbonate reacts with the isocyanate, a urea bond is generated in theory, forming the double cell region 11. The isocyanate index is the value obtained by dividing the number of moles of isocyanate groups in an isocyanate by the total number of moles of active hydrogen groups such as hydroxyl groups in a polyol and multiplying the result by 100, and is calculated as [NCO equivalent of isocyanate ÷ active hydrogen equivalent × 100].

[0030] The foaming agent is preferably water. When the polyol reacts with the isocyanate, water generates carbon dioxide gas, which causes foaming. The amount of water used as the foaming agent is 10 parts by weight or more relative to 100 parts by weight of the polyol, and the preferred amount of water is 10 to 15 parts by weight.

[0031] As the catalyst, a known urethane catalyst can be used in combination. For example, amine catalysts such as triethylamine, triethylenediamine, diethanolamine, dimethylaminomorpholine, N-ethylmorpholine, and tetramethylguanidine, tin catalysts such as stannous octoate and dibutyltin dilaurate, and metal catalysts such as phenylmercury propionate and lead octenate (also called organometallic catalysts), may be used alone or in combination of the amine catalyst and the metal catalyst. The amount of the amine catalyst is preferably 0.05 to 1.0 parts by weight relative to 100 parts by weight of the polyol. The amount of the metal catalyst is preferably 0 or 0.05 to 0.5 parts by weight.

[0032] The amount of sodium hydrogen carbonate is 5 to 30 parts by weight, more preferably 10 to 30 parts by weight, based on 100 parts by weight of polyol. By setting the amount of sodium hydrogen carbonate within the above range, the endothermic reaction can be carried out satisfactorily, and an increase in heat generation temperature during the production of polyurethane foam can be suppressed.

[0033] The organic solid acid, when used in combination with sodium hydrogen carbonate, exhibits a greater endothermic effect during the production of polyurethane foam, and can more effectively suppress the rise in heat-generating temperature of the polyurethane foam. The amount of the organic solid acid is preferably 1 / 30 to 1 / 60 of the amount of sodium hydrogen carbonate. The amount of the organic solid acid relative to 100 parts by weight of polyol is preferably 0.3 to 0.7 parts by weight relative to 100 parts by weight of polyol.

[0034] Examples of organic solid acids include citric acid, fumaric acid, malonic acid, stearic acid, pyruvic acid, phthalic acid, malic acid, maleic acid, succinic acid, and polybasic carboxylic acids having a hydroxyl group. The organic solid acid is not limited to one type, and two or more types may be used in combination. In particular, citric acid and malic acid (hydroxy acid) are more preferred organic solid acids in the present invention, and either one or both are used. In particular, malic acid is a preferred organic solid acid in the present invention. Note that either hydrate or anhydride of citric acid can be used.

[0035] Other auxiliaries may be added to the polyurethane foam raw material. Examples of auxiliaries include foam stabilizers and colorants. As the foam stabilizer, a foam stabilizer known for polyurethane foams can be used. Examples of the foam stabilizer include silicone foam stabilizers, fluorine foam stabilizers, and known surfactants. As the colorant, a carbon pigment or the like can be used depending on the application of the polyurethane foam.

[0036] The foaming method for producing polyurethane foam can be a molded foaming method in which the mixture is poured into a mold, or a slabstock foaming method, of which the slabstock foaming method is preferred for mass production. The slabstock foaming method is a method in which two liquid polyurethane foam raw materials are mixed in a mixer, discharged onto a belt conveyer, and foamed at atmospheric pressure and room temperature. The polyurethane raw material composition can be produced by a one-shot method, a prepolymer method, or the like. EXAMPLES

[0037] The following components were mixed in the proportions shown in Figure 4 and reacted and foamed to produce polyurethane foams of each Comparative Example and Example. The unit of the amount of each component added is parts by weight. Polyol: Polyether polyol, molecular weight: 3000, functionality: 3, hydroxyl value: 56.1 mg KOH / mg, product number: GP-3000, manufactured by Sanyo Chemical Industries, Ltd. Foaming agent: water Amine catalyst; Part No.: 33LV, Air Products Foam stabilizer: Silicone foam stabilizer, product code: B8110, manufactured by Goldschmidt Metal catalyst: Stannous octoate, product number: MRH110, manufactured by Johoku Chemical Industry Co., Ltd. Isocyanate: 2,4-TDI / 2,6-TDI=80 / 20, Product No.: Coronate T-80, manufactured by Nippon Polyurethane Industry Co., Ltd. ·Gypsum dihydrate; specific gravity 2.32, average particle size 40μm Sodium bicarbonate Citric acid Malic Acid

[0038] The maximum heat generation temperature of each comparative example and each example was measured as follows. A 38cm x 38cm x 24cm wooden box without a lid was prepared in advance, and a thermocouple was set in the center of the wooden box. Two liquids, a polyol compounding component and an isocyanate component, were prepared separately, and the two liquids were mixed and stirred with a propeller mixer. The reaction mixture was then poured into the wooden box, and a polyurethane foam was allowed to naturally foam at room temperature and atmospheric pressure.

[0039] In addition, in order to judge the reactivity during the production of polyurethane foams in each comparative example and each example, the cream time and rise time were measured by visual judgment. The cream time is the time it takes for the polyurethane foam raw material to change color from a mixed reaction liquid state at the time of mixing and casting to solidify and become a resin state. On the other hand, the rise time is the time it takes for the foam to expand and reach the maximum foam height from the time of mixing and casting. A short cream time indicates that the initial reaction is rapid, and a long cream time indicates that the initial reaction is slow. On the other hand, since the rise time is the time it takes to reach the maximum foam height, if the value obtained by subtracting the cream time from the rise time is small, it indicates that the reaction after the cream time is rapid, and conversely, if the value after subtraction is large, it indicates that the reaction after the cream time is slow.

[0040] The density (JIS K7220) and air permeability (JIS K6400-7) of the polyurethane foams of each of the comparative examples and examples were measured. In addition, the surface of the polyurethane foam of each Comparative Example and each Example was observed under a microscope to determine the presence or absence of double cell regions. If no double cell regions were present, they were indicated with "X", and if present, they were indicated with three grades of "△", "◯", or "◎" according to the amount of double cell regions present. "△" indicates that there is 1 or more but less than 10 double cell regions on a 5 cm x 5 cm surface, "◯" indicates that there are 10 or more but less than 20 double cell regions on a 5 cm x 5 cm surface, and "◎" indicates that there are 20 or more double cell regions on a 5 cm x 5 cm surface.

[0041] Comparative Example 1 is an example containing 100 parts by weight of polyol, 10 parts by weight of water as a foaming agent, 0.5 parts by weight of amine catalyst, 1.5 parts by weight of foam stabilizer, 0.15 parts by weight of metal catalyst, 170 parts by weight of isocyanate, an isocyanate index of 160, and 20 parts by weight of gypsum dihydrate, and is an example in which neither sodium hydrogen carbonate nor citric acid or malic acid as an organic solid acid is added. Comparative Example 1 has a maximum heat generation temperature of 178°C and a density of 11.2 kg / m 3 , breathability 1.37cc / cm 2 / sec, and the double cell area was marked "X".

[0042] Comparative Example 2 is the same as Comparative Example 1, except that 5 parts by weight of water, 0.35 parts by weight of metal catalyst, 93 parts by weight of isocyanate, and 5 parts by weight of sodium bicarbonate and 0.5 parts by weight of malic acid were mixed in place of the gypsum dihydrate in Comparative Example 1. Comparative Example 2 had a maximum heat generation temperature of 139°C and a density of 27.5 kg / m 3 , breathability 0.46cc / cm 2 / sec, and the double-cell region is "x", and the maximum heat generation temperature is lower and the density is higher than in Comparative Example 1. In addition, the amount of water blended as a foaming agent is small, so that a double-cell region is not obtained.

[0043] Comparative Example 3 is the same as Comparative Example 2, except that the amount of citric acid in Comparative Example 2 was changed to 15 parts by weight. Comparative Example 3 had a maximum heat generation temperature of 136°C and a density of 26.4 kg / m 3 , breathability 0.55cc / cm 2 / sec, and the double-cell region is "x", and the maximum heat generation temperature is low and the density is high, similar to Comparative Example 2. In addition, the blending amount of water as a foaming agent is small, so that a double-cell region is not obtained.

[0044] Comparative Example 4 is the same as Comparative Example 2, except that the amount of citric acid in Comparative Example 2 was changed to 30 parts by weight. Comparative Example 4 had a maximum heat generation temperature of 126°C and a density of 19.5 kg / m 3 , breathability 0.44cc / cm 2 / sec, and the double-cell region is "x", and the maximum heat generation temperature is low and the density is high, similar to Comparative Example 2. In addition, the blending amount of water as a foaming agent is small, so that a double-cell region is not obtained.

[0045] Example 1 is an example containing 100 parts by weight of polyol, 10 parts by weight of water as a blowing agent, 0.5 parts by weight of amine catalyst, 1.5 parts by weight of foam stabilizer, 0.15 parts by weight of metal catalyst, 170 parts by weight of isocyanate, an isocyanate index of 160, and 20 parts by weight of sodium bicarbonate, and containing neither citric acid nor malic acid as an organic solid acid. Example 1 has a maximum heat generation temperature of 183°C and a density of 14.8 kg / m 3 , breathability 1.85cc / cm 2 / sec, and the double cell region was rated "good." The double cell region provides good sound absorption. In addition, the maximum heat generation temperature is not extremely high, so the quality of the resulting polyurethane foam is good, and it has a small density and is lightweight.

[0046] Example 2 is the same as Example 1, except that the amount of sodium bicarbonate was reduced to 15 parts by weight and 0.5 parts by weight of malic acid was added. Example 2 has a maximum heat generation temperature of 165°C and a density of 10.8 kg / m 3 , breathability 1.07cc / cm 2 / sec, and the double cell region was rated as "◎". Example 2 uses a combination of 15 parts by weight of sodium bicarbonate and 0.5 parts by weight of malic acid, so the maximum heat generation temperature is lower than in Example 1, and the double cell region was rated as "◎". The double cell region provides good sound absorption properties. In addition, the density is small and the material is lightweight.

[0047] Example 3 is the same as Example 2, except that the amount of isocyanate was 149 parts by weight and the isocyanate index was 140. Example 3 had a maximum heat generation temperature of 160°C and a density of 11.6 kg / m 3 , breathability 0.81cc / cm 2 / sec, and the double cell region was "good". In Example 3, the isocyanate index was reduced from 160 in Example 2 to 140, and the double cell region was changed from "◎" in Example 2 to "good". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0048] Example 4 is the same as Example 2, except that the amount of isocyanate was 128 parts by weight and the isocyanate index was 120. Example 4 had a maximum heat generation temperature of 151°C and a density of 12.8 kg / m 3 , breathability 1.25cc / cm 2 / sec, and the double cell region was "△". In Example 3, the isocyanate index was reduced from 160 in Example 2 to 120, and the double cell region was changed from "◎" in Example 2 to "△". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0049] Example 5 is the same as Example 2, except that 0.5 parts by weight of citric acid was used instead of malic acid. Example 5 had a maximum heat generation temperature of 162°C and a density of 13.6 kg / m 3 , breathability 0.75cc / cm 2 / sec, and the double cell region was "good". In Example 5, the malic acid in Example 2 was replaced with citric acid, and the double cell region was changed from "◎" in Example 2 to "good". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0050] Example 6 is the same as Example 2, except that 0.25 parts by weight of citric acid and 0.25 parts by weight of malic acid were used in combination. Example 6 had a maximum heat generation temperature of 154°C and a density of 18.9 kg / m 3 , breathability 4.45cc / cm 2 / sec, and the double cell region was "good". In Example 6, 0.25 parts by weight of the 0.5 parts by weight of malic acid in Example 2 was replaced with citric acid, and the double cell region was changed from "◎" in Example 2 to "good". The double cell region improves sound absorption. Also, the density is slightly higher than the other examples.

[0051] Example 7 is the same as Example 2, except that the amount of isocyanate was 106 parts by weight and the isocyanate index was 100. Example 7 had a maximum heat generation temperature of 132°C and a density of 15.8 kg / m 3 , breathability 0.2cc / cm 2 / sec, and the double cell region was "△". In Example 7, the isocyanate index was lowered to 100, and the double cell region went from "◎" in Example 2 to "△". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0052] Example 8 is the same as Example 2, except that the amount of isocyanate was 191 parts by weight and the isocyanate index was 180. Example 8 had a maximum heat generation temperature of 166°C and a density of 12.9 kg / m 3 , breathability 2.01cc / cm 2 / sec, and the double cell region was "good". In Example 8, the isocyanate index was increased to 180, and the double cell region went from "◎" in Example 2 to "good". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0053] Example 9 is the same as Example 2, except that the amount of isocyanate was 212 parts by weight and the isocyanate index was 200. Example 9 had a maximum heat generation temperature of 167°C and a density of 13.1 kg / m 3 , breathability 5.98cc / cm 2 / sec, and the double cell region was "good". In Example 9, the isocyanate index was increased to 200, and the double cell region went from "◎" in Example 2 to "good". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0054] Example 10 is the same as Example 2, except that sodium hydrogen carbonate was used in an amount of 30 parts by weight. Example 10 has a maximum heat generation temperature of 134°C and a density of 12.7 kg / m 3 , breathability 0.97cc / cm 2 / sec, and the double cell region was rated as "◎". In Example 10, the amount of sodium bicarbonate was increased from 15 parts by weight in Example 2 to 30 parts by weight, but the double cell region was rated as "◎" like Example 2. The double cell region provides good sound absorption. In addition, the density is small and the material is lightweight.

[0055] Example 11 is the same as Example 2, except that the amount of water was 15 parts by weight and the amount of isocyanate was 247 parts by weight. Example 11 has a maximum heat generation temperature of 185°C and a density of 14.8 kg / m 3 , breathability 12.3cc / cm 2 / sec, and the double cell region was "good". In Example 11, the amount of water was increased from 10 parts by weight in Example 2 to 15 parts by weight, so the heat generation temperature was higher than in Example 2, and the double cell region was changed from "◎" in Example 2 to "good". The double cell region provides good sound absorption properties. In addition, the density is small and the material is lightweight.

[0056] Example 12 is the same as Example 11, except that sodium hydrogen carbonate was used in an amount of 30 parts by weight. Example 12 has a maximum heat generation temperature of 145°C and a density of 11.9 kg / m 3 , breathability 13.9cc / cm 2 / sec, and the double cell region was rated as "good." In Example 12, the amount of sodium bicarbonate was increased to 30 parts by weight, so the heat generation temperature was lower than in Example 11, but the double cell region was rated as "good" like in Example 11. The double cell region provides good sound absorption. In addition, the density is small and the material is lightweight.

[0057] Example 13 is the same as Example 2, except that the amount of malic acid was 0.3 parts by weight. Example 13 has a maximum heat generation temperature of 182°C and a density of 15.0 kg / m 3 , breathability 3.28cc / cm 2 / sec, and the double cell region was "good". In Example 13, the amount of malic acid was reduced from 0.5 parts by weight in Example 2 to 0.3 parts by weight, and the double cell region changed from "◎" in Example 2 to "good". Since it has a double cell region, the sound absorption properties are good. In addition, since the maximum heat generation temperature is not extremely high, the quality of the obtained polyurethane foam is good, and furthermore, the density is small and it is lightweight.

[0058] Example 14 is the same as Example 2, except that the amount of malic acid was 0.7 parts by weight. Example 14 has a maximum heat generation temperature of 157°C and a density of 15.0 kg / m 3 , breathability 2.05cc / cm 2 / sec, and the double cell region was "good". In Example 14, the amount of malic acid was increased from 0.5 parts by weight in Example 2 to 0.7 parts by weight, and the double cell region was changed from "◎" in Example 2 to "good". The double cell region improves sound absorption. In addition, the density is small and the material is lightweight.

[0059] Example 15 is the same as Example 2, except that sodium bicarbonate was used in an amount of 5 parts by weight. Example 15 has a maximum heat generation temperature of 186°C and a density of 13.8 kg / m 3 , breathability 2.85cc / cm 2 / sec, and the double-cell region was "△". In Example 15, the amount of sodium bicarbonate was reduced from 15 parts by weight in Example 2 to 5 parts by weight, and the double-cell region changed from "◎" in Example 2 to "△". In addition, the maximum heat generation temperature was higher than in Example 2, but was not extremely high, so the quality of the obtained polyurethane foam was good, and furthermore, the density was small and the weight was light.

[0060] The seven-point average sound absorption coefficient was measured at frequencies of 500-2000 Hz and 2500-10000 Hz for Example 2 having a double cell region, Comparative Example A, and Comparative Example B. Comparative Example A used a nonwoven fabric sound absorbing and insulating material (3M, Thinsulate TC, basis weight: 300 g / m 2 ), whereas Comparative Example B is a melamine resin foam (BASF, Basotect G+, basis weight: 300 g / m 2The test sample is 20 mm thick and has a basis weight of 300 g / m 2 The measurement method for the seven-point average sound absorption coefficient is JIS A1409:1998 (Method of measurement of sound absorption coefficient using the reverberation room method).

[0061] The measurement results of the seven-point average sound absorption coefficient are shown in FIG. 5. In Example 2, the sound absorption was good, with values ​​of 90% or more in both 500-2000 Hz and 2500-10000 Hz, whereas in Comparative Example A the sound absorption was 76.0% in 500-2000 Hz and in Comparative Example B the sound absorption was 86.4% in 500-2500 Hz, meaning that both Comparative Examples A and B had poor sound absorption. In this way, the examples have better sound absorption properties than the conventional nonwoven fabric or the comparative examples of melamine resin foam, due to the double cell region in the open cell structure of the polyurethane resin.

[0062] INDUSTRIAL APPLICABILITY The polyurethane foam of the present invention has good sound absorbing properties, is lightweight and has good quality, and is suitable for use in furniture, building materials, vehicle interior materials, sound absorbing materials, and the like. [Explanation of symbols]

[0063] 11: Double cell area 12: Matrix cell area

Claims

[Claim 1] A method for producing a polyurethane foam by mixing and reacting polyurethane foam raw materials including a polyol, an isocyanate, a blowing agent, and a catalyst, comprising: The polyurethane foam raw material contains sodium bicarbonate, A method for producing polyurethane foam, characterized in that the amount of water as the blowing agent is 10 parts by weight or more per 100 parts by weight of the polyol.

Citation Information

Patent Citations

  • Amplifier having controllable transmission amount and switching control characteristic curve

    JP1977004754A

  • Polyurethane foam having continuous cell structure

    JP2006199869A

  • Soft polyurethane foam

    JP2009051996A

  • Coated sound absorbing material

    JP2010122561A